Properties of Sinters Produced from Commercially Available Powder Mixtures - Borowiecka-Jamrozek J.; Lachowski J. (Archives of Foundry Engineering, 2016)
This paper discusses the mechanical properties of a material fabricated from commercially available metal powder mixtures designed for use as a metal matrix of diamond impregnated composites. The mixtures with the catalogue numbers CSA and CSA800 provided by a Chinese producer are suitable for experimental laboratory testing. The specimens were fabricated in a graphite mould using hot pressing. The material was tested for density, porosity, hardness, and tensile strength under static loading. A scanning electron microscope (SEM) was used to analyze the microstructure and cleavage fracture of broken specimens. It was essential to determine how the chemical composition and the fabrication process affected the microstructure and properties of the material. The properties of the sinters were compared with those of hot pressed specimens fabricated from sub-micron size cobalt powder (Cobalt SMS). Although the as-consolidated material is inferior to cobalt, it displays a favourable combination of hardness, yield strength and ductility, and seems to have a great potential for moderate and general purpose applications.